The Clinical Importance of Hyponatremia in Patients with Left Ventricular Assist Devices. Issue 9 (18th February 2021) - Kanelidis, Anthony J.; Imamura, Teruhiko; Yang, Benjamin; Miller, Tamari A.; Bharmal, Murtaza; Kim, Gene; Sayer, Gabriel; Uriel, Nir
Abstract : Hyponatremia is associated with increased morbidity and mortality in heart failure (HF) patients. The implication of hyponatremia during left ventricular assist device (LVAD) therapy remains unknown. In this retrospective study, consecutive LVAD patients implanted between April 2014 and March 2018 were stratified by the presence of hyponatremia (serum sodium <135 mEq/L) at 30 days post-LVAD. Incidence of HF readmissions and survival during 1-year follow-up were compared between the groups. Of 204 patients identified, 170 were included. Serum sodium levels improved significantly from pre-LVAD to 1-year post-LVAD (136 [133, 139] mEq/L to 137 [135, 140] mEq/L, p < 0.001). At 30 days, 35 patients (21%) were in the hyponatremia group. No difference was observed for 1-year survival between groups (77% vs. 81%, p = 0.66). However, the incidence of HF readmissions was significantly higher in the hyponatremia group (44% vs. 15%, p = 0.001). Among the patients with pre-LVAD hyponatremia (N = 60), those with normalized serum sodium levels (N = 42) had a lower incidence of HF readmissions compared with those with persistent hyponatremia (12% vs. 44%, p = 0.008). Hyponatremia in LVAD patients is associated with a higher incidence of HF readmissions. Further studies are needed to elucidate whether therapies directed at hyponatremia ( e.g., vasopressin antagonists) would improve outcomes in LVAD patients.